(untitled) (Psychology Travelogs, 2023)
The article presents the results of a theoretical study of the psychological features of the formation of professional plans among high school students. The essence of the concept of "professional plan" and its structure, which includes target, cognitive, personal-volitional, professional-activity and value components, are determined. In order to shift the emphasis of professional self-determination, which is focused on the labor market, to finding the meaning of personal development, we propose to highlight the value component in the structure of the professional plan. The main value orientation can be the desire to build a unique life, which is full of professional creativity and benefit to other people. In our opinion, all values are interrelated and are in a state of dynamic balance that depends on the individual. The professional plan is formed in accordance with the existing value orientations, when the individual begins to correlate the individual value system with the opportunities offered by society. Professional plans of high school students are, in their essence, not only an important structural organization of the personality at the stage of its self-determination, but can also play various other roles: the instigator of individual student actions; indicator of schoolchildren’s aspirations, which can be used to predict personality development, orient it towards a certain professional activity, etc. A variant of the scheme for building an individual professional plan for schoolchildren is offered. The levels and indicators of the formation of professional plans of high school students are highlighted, and career guidance measures are recommended in accordance with each of the levels.